Mental health and wellbeing of Australian police and emergency services employees. Issue 4 (21st April 2022) - Kyron, Michael J.; Rikkers, Wavne; Bartlett, Jennifer; Renehan, Emma; Hafekost, Katherine; Baigent, Michael; Cunneen, Rebecca; Lawrence, David
Abstract: Answering the Call, the Australian National Police and Emergency Services Mental Health and Wellbeing Study, surveyed 14, 868 Australian ambulance, fire and rescue, police, and state emergency service employees. Emergency services personnel had lower rates of mental wellbeing and higher rates of psychological distress and probable PTSD than the general adult population. Overall 30% had low wellbeing, 21% had high and 9% had very high psychological distress, and 10% had probable PTSD. An estimated 5% had suicidal ideation and 2% had a suicide plan in the past 12 months, while 16% binge drink at least weekly. Only one in five of those with very high psychological distress or probable PTSD felt they received adequate support for their condition. These findings highlight the risk of mental health conditions associated with work in the emergency services sector.